Cadmium uptake in native cacao trees in agricultural lands of Bagua, Peru - Oliva M. (2020)
Cadmium (Cd) contamination threatens cocoa farming in the province of Bagua in Amazonas, Peru. This study reports our assessment of Cd concentrations in cocoa farm soils, and in cocoa roots, leaves, testa, and cotyledon, thus evaluating the magnitude of the problem caused by Cd exposure. For our analysis, we sampled agricultural soil, cocoa roots, leaves and pods at 29 farms in the province of Bagua. Concentrations of Cd in each of the samples were measured and correlated with selected variables at each sampling site. Within our collection of samples, Cd levels showed great variability. In soil, Cd concentrations ranged between 1.02 and 3.54 mg kg-1. Concentrations of this metal within cocoa trees measured from roots, leaves, testa, and cotyledon, Cd ranged from 0.49 mg kg-1 to 2.53 mg kg-1. The cocoa trees exhibited variable degrees of allocation Cd from the soil to their tissues and thus considerable variation among themselves. We found that Cd amounts in roots were up to five times more concentrated than Cd levels in the soils and 2.85 times [Cd] the amounts found in cotyledon. Soil pH is a key variable enabling the uptake of this metal. Most importantly, our evaluation determined that measurements from the majority of farms exceeded the maximum permissible limits established by Peruvian and European legislation. © 2020 by the authors.